A millennium of ore mining and smelting in the eastern Harz: a geospatial database spanning from the medieval period to the 20th century - J. Keßels; A. Swieder; P. Schulte; P. Schulte; G. Alper; C. Tober; S. Friederich; F. Lehmkuhl (Eiszeitalter und Gegenwart)
The mid-mountain ranges are characterised by a medieval land occupation driven by various factors, which in turn affected the river systems. In particular, extraction and smelting activity led to distinct signals in floodplain sediments, serving as valuable tracers for reconstructing past environmental conditions and assessing anthropogenic impacts. This study creates the basis to link existing historical and geo-/montan-archaeological data with future geoscientific research for the Selke River catchment. A database of mines, smelters, and settlement structures was derived from (1) written sources, (2) old maps, and (3) a dataset of anthropogenic surface structures. The study focuses on the spatial alignment of the mining operations with the corresponding vein systems and their chronology and correlates the smelting activity with river kilometres and hydrological subregions. Ultimately, this research defines (a) three key areas that are characterised to varying degrees by mining activity and (b) discusses possible downstream impacts on overbank deposits from these historical mining locations.